ВИКОРИСТАННЯ ПОНЯТТЯ КОЕФІЦІЄНТУ ПОТУЖНОСТІ ЗАДЛЯ ОЦІНКИ ЕФЕКТИВНОСТІ ПРИСТРОЇВ КОРИГУВАННЯ ПЕРЕХІДНИХ РЕЖИМІВ МЕРЕЖІ - Чиженко, О.І.; Попович, О.М.; Трач, І.В.; Рибіна, О.Б. (Інститут електродинаміки НАН України, Київ, 2020)
The expansion of the concept of power factor, that  defined for circuits with periodic voltage and currents, to three-phase circuits with asymmetric non-periodic voltage and currents is justified. It is shown that this concept is advisable both when considering transients these occur in electric networks in the start-up modes of powerful asynchronous machines, and when evaluating the effectiveness of the use of various technical devices for these modes for correcting. References 6, figures 2.